2015
DOI: 10.1007/s40090-015-0053-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidation effect of ascorbic acid on mercury ions in blood sample using cyclic voltammetry

Abstract: A modification glassy carbon electrode was fabricated as biosensors by mechanical attachment with carbon nanotubes to detect the effect of different concentrations of ascorbic acid (AA) on mercury ions in blood of human healthy samples using cyclic voltammetric technique. The oxidation potential peak of mercury ions in blood medium was appeared at 0.2 V, while the same peak in KCl as a supporting electrolyte appeared at 0.25-0.3 V. It was observed that the different concentrations of AA which are added to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Electronic spectral properties also showed that the sulphur donor atom of L1 weakened the ligand field with respect to ligand-to-metal charge-transfer band. [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic spectral properties also showed that the sulphur donor atom of L1 weakened the ligand field with respect to ligand-to-metal charge-transfer band. [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic voltammetric technique was used by scientists to identify the impact of chemical compounds on the blood components during the exposure of the body to pollutants or drugs [1][2][3][4][5][6]. Recent studies have confirmed that antibiotic compounds after being converted to nanoparticles showed great effect on the elimination of different types of bacteria which cause diseases [7].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical studies by cyclic voltammetric method with modified working electrodes were realized for the redox current peaks of the pollutants in the blood medium [1][2][3][4][5][6][7]. Children polluted with higher levels of metals, such as lead and antimony in their urine suffered from more severe autism, suggesting that metal levels in their bodies may contribute to its seriousness [8][9][10].…”
Section: Introductionmentioning
confidence: 99%